Cholesterol-induced colorectal cancer progression and its mitigation through gut microbiota remodeling and simvastatin treatment - Xiaoliang Xie; Wenjing Wang; Haiming Zhang; Shaohui Zhao; Na Zhang; Ying Gao; Quanxia Liu; Xiaomei Chen (BMC Cancer)
Abstract Background Elevated serum cholesterol levels are linked to an increased risk of colorectal adenomas and colorectal cancer (CRC), yet the role of serum low-density lipoprotein (LDL) in CRC development remains unclear. This study explores the impact of cholesterol on tumor growth and the potential therapeutic effects of Lactobacillus and Simvastatin. Methods We utilized a cecal tumor xenograft mouse model with Ldlr−/− mice to assess the effects of high cholesterol levels on tumor growth. Additionally, the role of gut microbiota remodeling and cholesterol-lowering strategies was investigated using Lactobacillus supplementation and Simvastatin treatment. Results Ldlr−/− mice on a high-cholesterol diet developed significantly larger tumors (P < 0.05) and exhibited exacerbated malignancy, as indicated by HE and Ki-67 staining. Lactobacillus supplementation reduced tumor growth (P < 0.05), lowered serum cholesterol levels, and altered the gut microbiota composition, increasing the relative abundance of beneficial bacterial taxa. Simvastatin treatment reduced PD-L1 expression in CRC cells by lowering cholesterol levels, which was associated with decreased CRC proliferation, reduced serum LDL levels, and enhanced T cell infiltration in the tumor microenvironment. Conclusion Elevated serum cholesterol promotes CRC progression, while gut microbiota remodeling through Lactobacillus supplementation and cholesterol-lowering interventions, such as Simvastatin, show potential in mitigating tumor growth and enhancing antitumor immune responses. These findings highlight the importance of cholesterol management in CRC treatment strategies.